Effect of loach paste on the liver and immune organs of D-galactose-induced ageing mice - Haiying Liu (Taylor & Francis Group, 2018)
We examined the effects of loach paste (LP) on liver and immune organs of d-galactose (DG)-induced aging mice. The results showed that LP can alleviate the atrophy of spleen and thymus, and restore the blood glucose levels. LP was particularly beneficial to liver. Liver indices and activities of aspartate aminotransferase, alanine aminotransferase, and alkaline phosphatase reduced with high doses of LP. Moreover, LP can improve the antioxidant system in liver by increasing the activities of total superoxide dismutase, glutathione peroxidase, and catalase, reducing malondialdehyde concentration. Furthermore, LP can improve immunity and reduce the inflammation of liver. The swelling of liver cells was alleviated and the cell arrangement returned to normal in the LP group. In addition, gene expressions of HSP70 and tumour necrosis factor-α (TNF-α) in liver which can promote inflammatory cytokine decreased significantly. Thus, regular LP intake effectively relieved DG-induced oxidative stress and alleviated liver and immune organs damage.